The role of stacking on the electronic structure of MoSe2 at small twist angles - S Patra; M Das; P Mahadevan (JPhys Materials, 2023)
We consider two high symmetry stackings AA and AB and examine the changes induced in the electronic structure by considering small angles of rotation of 3.48° from both these stackings. In both cases we largely recover the low energy electronic structure of the untwisted limit. We additionally find flat bands emerging above the dispersing bands. Surprisingly, while the rotation from the AA end leads to one flat band above the highest occupied band at Γ, one finds two flat bands emerging for small rotations from the AB end. Examining the real space localisation of the flat bands allows us to discuss the origin of the flat bands in terms of quantum well states and qualitatively understand the dependence of the number of flat bands found on the twist angle.